Mutação (in)constitucional do controle difuso de constitucionalidade: legítima evolução ou patente violação ao sistema de direitos e garantias fundamentais? - Zanotti, Bruno Taufner (2010)
It is intended from the questioning of the theory of abstractiveness of the diffuse control of constitutionality to qualify people as an effective instrument of power legitimacy of the democratic state. Based on a discursive theory of law, we seek to understand and demonstrate some harmful consequences of this new model of constitutionality, which blocks the public of an important channel of access to Jurisdiction and individual analysis of each concrete case. We have initially decided to analyze the legitimacy of the democratic creation of Law and its influence on the popular participation throughout the legislative process, so as to subsequently, extend this understanding and adapt it to Judicial Power, in order to also imbue it with democratic principle. An open society of interpreters enables the expansion of the hermeneutic constitution, which releases the magistrate from the bonds of a strictly closed vision while opening it to a pluralistic and democratic interpretation. Along the way, the premises of the procedural paradigm of the democratic legal state were set, inasmuch the legal autonomy of citizens only become a real factor of legitimacy to the extent that they can understand themselves as co-authors of the law, to which they submit themselves, since they are also the natural recipients of such rules. The democratic process must be founded from the establishment of the Constitutional Power up to the way the spheres of power act. Based on the performed analysis and the evolution of the study, we were able to reach the following conclusions: 1. A qualitative view of people as a constant feature in construction should influence the activities of the legislative, administrative and jurisprudential capacity. 2. The internal cohesion between public autonomy and private autonomy is the foundation of legitimacy of law and calls for people's participation in the decision-making. 3. Deliberative democracy is the appropriate locus for the institutionalization of instruments that qualify and make it possible to people to integrate the democratic procedure. 4. Court activity, as jurisdiction of power should legitimize such decision, as it occurs with legislative duties in the democratic process. 5. The theory of abstractiveness of diffuse control of constitutionality violates the legal autonomy of citizens, and identifies the Supreme Court as the sole owner of the constitutional subject and turns citizens into clients of the authoritarian thinking of a few judges.